The Effect of Animated Video Education on Dental and Oral Health Behavior Among Elementary School Students in Deli Serdang Regency - Irgi Ariyani; Salianto Salianto; Zulkarnaen Zulkarnaen; Nurhayati Nurhayati (Jurnal Manajemen Informasi Kesehatan (Health Information Management), 2026)
Background: Oral health plays an important role in children's overall well-being, influencing their ability to eat, communicate, learn, and participate in daily activities. However, inadequate oral hygiene knowledge and poor oral health practices remain common among school-aged children, increasing the risk of preventable oral diseases. Animated video-based education has emerged as a promising approach because it combines visual and auditory learning elements that can attract children's attention and facilitate understanding. This study aimed to examine the effect of animated video education on oral health maintenance behavior among students at SD Negeri 106785, Sunggal District, Deli Serdang Regency, North Sumatra. Method: This study employed a pre-experimental design with a one-group pretest-posttest approach. A total of 57 students were recruited using total sampling. Oral health maintenance behavior was assessed using a 10-item questionnaire with acceptable validity (r-value > 0.3601) and reliability (Cronbach's Alpha = 0.777). Data were analyzed using descriptive statistics and simple linear regression to examine the association between the educational intervention and behavioral outcomes. Result: The mean oral health maintenance behavior score increased from 5.26 before the intervention to 7.23 after the intervention. Statistical analysis showed a significant improvement in behavior following animated video education (F = 80.882; p < 0.001). The regression model yielded an R² value of 0.595, indicating a substantial association between the intervention and post-intervention behavior scores. Conclusion: Animated video-based education was associated with improved oral health maintenance behavior among elementary school students. The findings suggest that animated videos may serve as an effective and practical educational medium for promoting oral health behaviors in school settings. Further studies using controlled experimental designs are recommended to confirm the effectiveness of this intervention.